Radiographic features of periapical cysts and granulomas - Zain, R.B.; Roswati, N.; Ismail, K. (1989)
Many studies have been reported on radiographic lesion sizes of periapical lesions. However no studies have been reported on prevalences of subjective radiographic features in these lesions except for the early assumption that a periapical cyst usually exhibit a radiopaque cortex. This study is conducted to evaluate the prevalences of several subjective radiographic features of periapical cysts and granulomas in the hope to identify features that maybe suggestive of either diagnosis. The results showed that a regular (circular or semi-circular) radiographic outline is likely to be a periapical cyst while an irregular radiographic outline is not indicative of either a cyst or a granuloma. The association between the regular/irregular radiographic outline and the type of periapical lesion was found to be statistically significant (p less than 0.001). The associations of two other radiographic features and the type of periapical lesion were found to be just statistically significant (p less than 0.01). These features are the symmetry/asymmetry of the radiolucency in relation to the apex and the funnel-shaped/angular-shaped extension of the radiolucency. The widely accepted criteria that the possession of a radiopaque cortex surrounding the radiolucency can discriminate between a periapical cyst and granuloma cannot be statistically supported in this study.